2011
DOI: 10.1152/jn.00954.2010
|View full text |Cite
|
Sign up to set email alerts
|

Task- and time-dependent modulation of Ia presynaptic inhibition during fatiguing contractions performed by humans

Abstract: Baudry S, Maerz AH, Gould JR, Enoka RM. Task-and timedependent modulation of Ia presynaptic inhibition during fatiguing contractions performed by humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 37 publications
2
43
3
Order By: Relevance
“…Previous work has shown that the strategies used to sustain force and position control differ during submaximal isometric contractions, even when the net muscle torque is similar across conditions. The rates of change in motor unit activity and modulation of reflex pathways, for example, are more rapid during position control (Baudry et al 2011;Mottram et al 2005;Rudroff et al 2010), which results in a briefer endurance time for a position task at low to moderate target forces (Baudry et al 2009;Hunter et al 2005Hunter et al , 2008Klass et al 2008;Rudroff et al 2010). Given that the motor performance capabilities of the nondominant arm of left-handed subjects are superior to those of righthanded subjects (Brouwer et al 2001;Caroselli et al 2006;Hoffmann 1997;Hoffmann et al 1997;Judge and Stirling 2003;Przybyla et al 2012), we expected to find that lefthanded subjects would exhibit less of a difference in the endurance time for sustained isometric contractions that have been shown to involve unique control strategies.…”
mentioning
confidence: 99%
“…Previous work has shown that the strategies used to sustain force and position control differ during submaximal isometric contractions, even when the net muscle torque is similar across conditions. The rates of change in motor unit activity and modulation of reflex pathways, for example, are more rapid during position control (Baudry et al 2011;Mottram et al 2005;Rudroff et al 2010), which results in a briefer endurance time for a position task at low to moderate target forces (Baudry et al 2009;Hunter et al 2005Hunter et al , 2008Klass et al 2008;Rudroff et al 2010). Given that the motor performance capabilities of the nondominant arm of left-handed subjects are superior to those of righthanded subjects (Brouwer et al 2001;Caroselli et al 2006;Hoffmann 1997;Hoffmann et al 1997;Judge and Stirling 2003;Przybyla et al 2012), we expected to find that lefthanded subjects would exhibit less of a difference in the endurance time for sustained isometric contractions that have been shown to involve unique control strategies.…”
mentioning
confidence: 99%
“…During sustained maximal contractions, H-reflex amplitude declines gradually, most likely due to group III and IV afferent input (Duchateau et al 1993). H-reflex paired-pulse suppression, on the other hand, demonstrates a biphasic pattern, with facilitation of the conditioned H early during fatigue and a return of H-reflex suppression as exhaustion approaches (Baudry, Maerz, Gould and Enoka 2011). During intermittent contractions, interposed rest cycles limit metabolite accumulation and H-reflex amplitude increases with fatigue (Loscher et al 1996, Nordlund et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…One previous report used these two conditioning methods in the upper extremity during a pair of static (isometric) fatigue tasks (Baudry et al 2011). Unlike our dynamic fatigue task, these authors observed pre/post fatigue changes in H-reflex depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Input from Ia afferents to the active motor neuron pool can be inhibited due to the depolarization of primary afferent fibers by interneurons and consequently affect the activation of the motor units to the targeted muscle. 47,48 Further, depending on the task that is to be performed, whether position control or force control, older adults demonstrate a decreased ability to regulate presynaptic inhibition compared with young adults. For example, Baudry and Enoka 47 reported that the ability of older adults to regulate presynaptic Ia afferent inhibition was reduced when individuals were tasked to control hand position while supporting a mass (position control) compared with exerting the same force against a rigid constraint (force control).…”
Section: Discussionmentioning
confidence: 99%